Practical Tourism Research. 2nd Edition - Benítez-Aurioles, Beatriz (Investigaciones Turísticas, 2019)
Reseña de Practical Tourism Research. 2nd Edition. Stephen L.J. Smith. Cabi Tourism Texts; Wallingford, Oxfordshire; Boston, MA. 2017. ISBN: 9781780648873. 268 páginas.